Challenges in Accommodating Volume Change of Si Anodes for Li‐Ion Batteries. Issue 11 (31st August 2015) - Ko, Minseong; Chae, Sujong; Cho, Jaephil
Abstract: Si has been considered as a promising alternative anode for next‐generation Li‐ion batteries (LIBs) because of its high theoretical energy density, relatively low working potential, and abundance in nature. However, Si anodes exhibit rapid capacity decay and an increase in the internal resistance, which are caused by the large volume changes upon Li insertion and extraction. This unfortunately limits their practical applications. Therefore, managing the total volume change remains a critical challenge for effectively alleviating the mechanical fractures and instability of solid‐electrolyte‐interphase products. In this regard, we review the recent progress in volume‐change‐accommodating Si electrodes and investigate their ingenious structures with significant improvements in the battery performance, including size‐controlled materials, patterned thin films, porous structures, shape‐preserving shell designs, and graphene composites. These representative approaches potentially overcome the large morphologic changes in the volume of Si anodes by securing the strain relaxation and structural integrity in the entire electrode. Finally, we propose perspectives and future challenges to realize the practical application of Si anodes in LIB systems. Abstract : Crack of doom : Si anodes suffer a large volume variation during cycling, resulting in mechanical fractures and unstably formed SEI products. Therefore, managing the volume change remains a critical challenge for improving the battery performance to enable practical application of Si anodes in LIBs. This article reviews the challenges for accommodating the volume change of Si anodes and presents perspectives and challenges for future research.